Broad valleys and barrier dams in upstream Brahmaputra efficiently retain Tibetan-sourced sediments: Evidence from palaeoflood records. (1st June 2022) - Hu, Kaiheng; Wei, Li; Yang, Anna; Wu, Chaohua; Zhang, Qiyuan; Liu, Shuang; Wang, Zhang
Abstract: Recent studies confirm that more than 50% of the sediment load of the Brahmaputra River originates from the Namche Barwa massif, whose area is just 2–3% of the total drainage area. This sediment flux anomaly cannot be attributed to only rapid erosion caused by extreme outburst floods because the young cooling age population of the Namche Barwa source sediment is disproportionally high even in the modern sediment transported by normal river flows. We propose a new mechanism for this anomaly by integrating new findings of palaeoflood sedimentary records with previous field surveys around Yigong Lake, a residual dammed lake in the lower Yigong River which is a major tributary of the Brahmaputra River, in the southeastern margin of Tibet. The magnitude of the palaeoflood event upstream of the lake, with a peak discharge of 64, 500 m 3 /s estimated by using hydraulic reconstruction approaches, is far smaller than that of downstream flood events. Tibetan source sediment transport is truncated by the juxtaposition of broad valleys and barrier dams on the edge of the highly exhumated region with cooling ages of <2 Ma. This juxtaposition has three effects: trapping large amounts of the upstream sediment load, flattening the hydrograph of upstream extreme floods, and enlarging the magnitude of downstream outburst floods. Hence, the spatial consistency of the broad valley-dammed lake systems in the Rivers in the young cooling region probably shed light on understanding the sediment source conundrum for the Brahmaputra River. Highlights: A ∼9.2 ka extreme flood was identified upstream of Yigong Lake. Three effects of broad valley-lake system on the southeastern margin of Tibet. Tibetan sediment is truncated by juxtaposition of broad valleys and barrier dams.